KOMPOSISI DAN STRUKTUR VEGETASI MANGROVE DI PANTAI TANJUNG BASTIAN KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR - LEDHENG, LUDGARDIS; ARDHANA, IPG; SUNDRA, I KETUT (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2)
This research was carried out in Tanjung Bastian Beach, on February and March 2009. The aim of this research is to identify composition, structure and environment condition of mangrove vegetation in Tanjung Bastian Beach, North Middle East Regency, Province of Nusa Tenggara Timur.Research method used was observation and squares sampling technique that straight with beach line toward upland. Data was analyzed using vegetation analysis.The result of this research shows that Tanjung Bastian mangrove with mangrove thickness about 50 – 1000 m, arranged by 29 type mangrove vegetation which consist of 11 major mangrove, 5 minor mangrove and 13 mangrove associate. In the A location where the activity was high, Significant Value Index of plant level and highest plant, dominated by Bruguiera gymnorrhiza 79,49% and 99,88%, while for pole level and seedling, dominated by Rhizophora apiculata 106,93% and 50,02%. In B location, the highest INP of plant level, pole and seedling dominated by B. gymnorrhiza with score 62,03%; 99,57%; 108,52% and 48,22%. B. gymnorrhiza also dominates for plant level, pole and seedling in C location with each value 55,05%; 49,68%; 69,39% and 35,81%. B. gymnorrhiza is predicted to dominate mangrove trees population in the Tanjung Bastian mangrove area. This is indicated with high population of seedling level and pole in the location with medium activity level and nature forest. Vegetation Variety Index Tanjung Bastian beach mangrove range between 0.6774 -1,1513, catagorized as poor.Destruction level of mangrove vegetation in C location nature forest is still in good category, while for B and A location medium and high activity is categorized as damage mangrove forest according to SK MENLH RI No. 201 Year 2004, about Standard Criteria and Standard of Mangrove Damage Principle.Condition of basic substrate in Tanjung Bastian mangrove dominated by sandy loam with organic-C range between 0,40 -4,04%. N value, range between 0,03 -0.12%, P, 12,72 -44,47ppm, while K rate, 202,81 – 671,42 ppm. Mangrove temperature condition range between 28,87 – 30,950C, with pH rate 7,5 -8,0 and salinity range between 30 -33%o.
Keywords: Mangrove vegetation, composition and structure, destruction level